PENERAPAN PEMBELAJARAN AKTIF, INOVATIF, KREATIF, EFEKTIF, MENYENANGKAN GEMBIRA DAN BERBOBOT (PAIKEM GEMBROT) UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR SISWA KELAS X.B MA NW SIKUR MATERI POKOK LOGIKA - milaska, Hafiz Zulfahrizal; Yulianti, Sri (Media Pendidikan Matematika, 2014)
This study is aimed to know whether or not the use of learning active, creative, effective, pleasure, and weighted to improve the students learning achievement on the main material of logic Data collection methods used were observation, interviews, documentation and testing. The result of the data analysis approach Paikem fatÂ  was able to improve the students learning achievement on the main material of logic at the first grade student of MA NW Sikur in Academic Year 2013/2014